Dampak Perkembangan IPTEK terhadap Perubahan Sosial dan Dinamika Kehidupan - Meysi Wulandari. AP; Putri Sidahtilla Umma; Indah Ratu Sehati; Sani Safitri (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Modernization is a transformation process that encourages changes in various aspects of life, including in the field of science and technology (IPTEK). The development of science and technology has had a significant impact on people's social, economic, educational and communication lives. This research uses a qualitative approach with a literature study method to analyze how advances in science and technology affect social dynamics. The results show that technological developments provide great benefits, such as easy access to information, increased efficiency in various sectors, and the opening of new economic opportunities. However, on the other hand, modernization also presents challenges, such as reduced quality of social interactions, data security risks, and technology access gaps. Therefore, digital awareness and appropriate policies are needed to minimize the negative impacts and optimize the benefits of technological progress. It can be interpreted that science and technology has become a major factor in shaping the pattern of life of modern society, so its utilization needs to be directed wisely so that it can make a positive contribution to social and economic development.